2016
DOI: 10.1021/acs.joc.6b01160
|View full text |Cite
|
Sign up to set email alerts
|

Ru(II)-Catalyzed C–H Activation: Amide-Directed 1,4-Addition of the Ortho C–H Bond to Maleimides

Abstract: Maleimide has been used as a selective coupling partner to generate conjugate addition products exclusively. The typical Heck-type oxidative coupling that occurs when alkenes are used is avoided by choosing maleimide as an alkene, which cannot undergo β-hydride elimination due to the unavailability of a syn-periplanar β-hydrogen atom. The amide nitrogen, which is notorious for undergoing tandem reactions to generate spirocyclic or annulation products under cross-coupling conditions, remains innocent in this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(28 citation statements)
references
References 47 publications
0
26
0
2
Order By: Relevance
“…This reaction can also be performed from the corresponding allylic alcohols in the presence of an additional oxidant under ruthenium or rhodium catalysis [81] and maleimides can be used as alkylating agents. [82] Iridium catalysis was also shown to provide remarkably efficient systems for the branched-selective ortho-alkylation of benzamides with ar ange of alkenes-the formation of branched products is much more challenging to achieve. Indeed, the Bower group showed that monosubstituted alkenes can be efficiently used for the branched-selective ortho-alkylation of aseries of aromatic amides using acationic iridium(I) catalyst modified with an electron-deficient biphosphine ligand with aw ide bite angle [Scheme 17, Eq.…”
Section: Alkylation Of Aromatic Amides With Alkenesmentioning
confidence: 99%
“…This reaction can also be performed from the corresponding allylic alcohols in the presence of an additional oxidant under ruthenium or rhodium catalysis [81] and maleimides can be used as alkylating agents. [82] Iridium catalysis was also shown to provide remarkably efficient systems for the branched-selective ortho-alkylation of benzamides with ar ange of alkenes-the formation of branched products is much more challenging to achieve. Indeed, the Bower group showed that monosubstituted alkenes can be efficiently used for the branched-selective ortho-alkylation of aseries of aromatic amides using acationic iridium(I) catalyst modified with an electron-deficient biphosphine ligand with aw ide bite angle [Scheme 17, Eq.…”
Section: Alkylation Of Aromatic Amides With Alkenesmentioning
confidence: 99%
“…Prabhu and co‐workers developed an amide‐directed, Ru(II)‐catalyzed ortho‐ alkylation of aromatic amides to prepare 3‐arylsuccinimides (Scheme ) . The reaction was carried out in DCE as solvent with [RuCl 2 ( p ‐cymene)] 2 as catalyst, AgBF 4 as activator, Cu(OAc) 2 ⋅H 2 O as acetate salt and AcOH as protonation source at 100 °C.…”
Section: Ortho‐c–h Functionalization Of Aromatic Amidesmentioning
confidence: 99%
“…In 2016, Prabhu's group reported ortho alkylation of benzamide derivatives with maleimides catalyzed by the Ru(II) arene complex . When N ‐methylbenzamide ( 18 a ) was treated with N ‐ethylmaleimide ( 19 a ) in the presence of [{RuCl 2 (p‐cymene)} 2 ] (5 mol%), AgBF 4 (20 mol%), Cu(OAc) 2 ⋅ H 2 O (1.5 equiv) and AcOH (10 equiv) at 100 °C in DCE, an ortho alkylated benzamide derivative 20 a was observed in 91% yield (Scheme ).…”
Section: Ortho Alkylation Of Aromatics With Maleimidesmentioning
confidence: 99%